A study on the distribution coefficient of bromide ions from aqueous solution on ion exchange resins Duolite A-101D and Duolite A-102D. (12th October 2009) - Singare, P.U.; Lokhande, R.S.; Kolte, A.R.
The ion exchange resins Duolite A-101D and Duolite A-102D in bromide form were equilibrated separately with labelled radioactive bromide ion solutions of different concentrations varying from 0.005 M to 0.100 M in the temperature range of 25.0°C to 45.0°C. The Kd values of bromide ions for Duolite A-102D were higher than that for Duolite A-101D under identical experimental conditions. The difference in Kd values of bromide ions for the two resins is mainly because of the swelling pressure, which depends on their water-holding capacities.